MODELLING OF N-DODECANE CATALYTIC HYDROISOMERIZATION USING PFR REACTOR FOR BIO JET FUEL PRODUCTION - Rafli Fadhilah, Muhammad
Indonesian jet fuel demand in 2018 was 5.717.729 KL which amounted to 8,61% its transportation energy consumption. National production capacity couldn’t meet thedemand which led to the import of 1.467.000 KL. Indonesia’s government’s General National Energy Plan stipulates that by 2025 and 2050 0.1 million KL and 2.7 million KL of bio-jet fuel will be produced nationally, demanding for the development bio-jet fuel production technologies than can meet commercial jet fuel standards. The vast availability of oil palm in Indonesia and the compactability of the length of palm kerel oil’s (PKO) carbon chain makes it suitable candidate for bio-jet synthesis. The simulation is conducted to model catalytic n-dodecane hydroisomerization of the hydrodeoxygenation product in a PFR type reactor using 0.5% Pt/US-Y catalyst. Sensitivity analysis is conducted on the effects of feed temperature, GHSV, feed pressure, and H2 to n- dodecane molar ratio. The model is constructed using Python 3 programming language with physical datas obtained from ASPEN Plus. Among the varied paramteres the system showed to be most sensitive to feed temperature. The model also shows that Jet A freezing point specification is achieved at a maximum conversions of 72,97% while flash point is achieved at conversions below 33,22%. Further blending, recycling, or change in feed compositionis required to achieve Jet A specifications.